Progress or Mistake? - Unnur Birna Karlsdóttir (Septentrio Academic Publishing, 2021)
This article focuses on the ideas behind the introduction of reindeer to Iceland, how the Danish authorities played a role and the attitudes that prevailed among Icelanders towards this new species in Icelandic nature. The Danish authorities had reindeer exported from Finnmark in Norway to Iceland in the late eighteenth century. They adapted to the Icelandic environment and grew in numbers, except for the first imported little flock, which seems to have died out soon. The idea of bringing reindeer to Iceland came from a few Icelandic officials, who asked the Danish authorities for support. The reindeer kept themselves in the remote heaths and highlands in the districts where they roamed free from the beginning. Nevertheless, in harsh winters, they fled the highlands and came down to the lowlands to graze. This caused frustration among farmers, who complained to the authorities and demanded permission to hunt reindeer to defend their grazing land and obtain reindeer meat for their households.